2016
DOI: 10.1080/10790268.2016.1180098
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and perceptual effects of precooling in wheelchair basketball athletes

Abstract: Objective: To investigate the physiological and perceptual effects of three precooling strategies during preexercise rest in athletes with a spinal cord injury (SCI). Design: Randomized, counterbalanced. Participants were precooled, then rested for 60 minutes (22.7 ± 0.2°C, 64.2 ± 2.6%RH). Setting: National Wheelchair Basketball Training Centre, Australia. Participants: Sixteen wheelchair basketball athletes with a SCI. Interventions: Participants were precooled through; 1) 10 minutes of 15.8°C cold water imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…From a theoretical perspective, cold fluid or ice slurry ingestion should also be beneficial in populations with a physiological disruption to sweating, such as athletes with a spinal cord injury [ 68 , 69 ], burn injuries [ 70 72 ] or following a sympathectomy procedure [ 73 ]. In all situations, the maximum proportion of the skin surface that can be physiologically saturated with sweat (i.e.…”
Section: How Does Cold Fluid or Ice Slurry Ingestion Impact Human Heamentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical perspective, cold fluid or ice slurry ingestion should also be beneficial in populations with a physiological disruption to sweating, such as athletes with a spinal cord injury [ 68 , 69 ], burn injuries [ 70 72 ] or following a sympathectomy procedure [ 73 ]. In all situations, the maximum proportion of the skin surface that can be physiologically saturated with sweat (i.e.…”
Section: How Does Cold Fluid or Ice Slurry Ingestion Impact Human Heamentioning
confidence: 99%
“…The decrease in sweating that accompanies the increase in internal heat loss with a cold/ice drink would therefore have a much smaller impact on heat dissipation and yield an improved net cooling effect compared with an athlete with a completely intact sweating apparatus. While the pre-exercise ingestion of ice slurries has been proven to be moderately effective in reducing core temperature prior to the onset of exercise in wheelchair athletes [ 68 ], to the best of our knowledge no existing studies have examined the influence of fluid temperature during exercise in the heat on the development of exercise-induced hyperthermia in these populations.…”
Section: How Does Cold Fluid or Ice Slurry Ingestion Impact Human Heamentioning
confidence: 99%
“…Although athletes with tetraplegia experience a heightened thermal response during exercise compared to the able-bodied, 3 to date eleven studies [10][11][12][13][14][15][16][17][18][19][20] have addressed the application of cooling methods in individuals with a SCI 21 . Webborn et al 10,14 investigated the use of ice vests prior to and during an intermittent arm-cranking protocol resulting in a lowered gastrointestinal temperature and increased time to exhaustion compared to no cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Only one published study has reported a cooling strategy involving ice ingestion in people with SCI. Forsyth et al (2016) studied whole body water immersion for 10 min that excluded the head and neck, ingesting 6.8 g/kg body mass (BM) of ice, or ice ingestion along with wearing an ice towel followed by rest at 22°C. The core temperature of participants that ingested ice while wearing an ice towel was lower than in those immersed in water.…”
Section: (2001)mentioning
confidence: 99%
“…SCI above the T6 level is likely to cause autonomic dysreflexia such as hypertension or bradycardia due to extension or fullness of the urinary bladder (Theisen, 2012). A study by Forsyth et al (2016) evaluated ice ingestion in persons with SCI with the volume ingested based on a previous study (Ihsan et al, 2010) in ablebodied persons. In this study, although three participants had SCI above the T6 level, no voiding problems or autonomic dysreflexia was observed.…”
Section: (2001)mentioning
confidence: 99%